Assessment of Tuber Yield Stability and Adaptability of Some Elite Yam Genotypes in the Guinea Savannah Ecology of Northern Ghana - Joseph Adjebeng-Danquah; Kwabena Acheremu; Emmanuel Boachie Chamba; Freda Ansaah Agyapong; Alhassan Sayibu (International Journal of Agronomy)
Studies were conducted to determine tuber yield stability and adaptability of some elite yam (Dioscorea sp.) genotypes in northern Ghana. Ten elite exotic yam genotypes alongside one locally cultivated farmer-preferred variety, Laribako, were grown in five environments between 2010 and 2012. These 11 genotypes were arranged in a randomised complete block design with three replications and assessed for tuber yield and yield components. Analysis of variance indicated significant p<0.05 genotypic variation for tuber yield and the yield components studied. Genotype × environment interaction effect was significant p<0.05 for tuber yield and mean tuber weight but not significant p>0.05 for number of tubers per mound. Apart from genotype 95/18922, all the exotic genotypes had significantly p<0.05 higher tuber yields than the local check, Laribako. The highest tuber yield (16.03 t ha−1) across environments was obtained from 96/19158 followed by 95/00594 (14.9 t ha−1). According to the additive main effect multiplicative interaction (AMMI) analysis, genotype (G), environment (E), and GxE interaction, respectively, explained 39.71%, 36.03%, and 24.26% of the total sum of squares for tuber yield. For number of tubers per plant, GxE effect explained the greatest percentage (60.46%) of the total sum of squares compared to genotype effect (22.00%) and environment effect (17.54%). The local variety, Laribako, was more stable across all environments though low yielding compared to the exotic genotypes. Three genotypes, 95/19158, 95/19177, and 96/02025, were more stable across environments than the other exotic genotypes. Genotype 95/18544 was the most sensitive and for that matter responded positively in the favorable environments. The study identified genotypes with specific and general adaptation potential across different environments for tuber yield that can be further tested in on-farm trials for possible release.